A comparative study of the antibiotic resistance pattern between the natural and clinical isolates based on whole cell protein profiling by SDS-PAGE - Islam, Tanim (BRAC University, 2016)
This thesis report is submitted in partial fulfillment of the requirement for the degree of B.Sc in Microbiology, 2016.